Farm to school of Park County : a journey from program to nonprofit (C) - Cates, Karen L.; Howard, Liz Livingston (London : Kellogg School of Management, 2019)
The third in a four part case series, this case describes how Farm to School's board developed a strategic plan and establishes committees. However, the board members and leaders start to feel fatigue in the face of the demands of a startup organization, leading to questions about what is truly strategic and how work will be completed.
Originally Published InCates, K. L., & Howard, L. L. (2019). Farm to School of Park County: A Journey from Program to Nonprofit (C). 5-418-751(C). Evanston, IL: Kellogg School of Management, Northwestern University.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business planning; Industrial organization